Combining mussel with fucoidan as a supplement for joint pain and prediabetes: Study protocol for a randomized, double-blinded, placebo-controlled trial - Tay, Audrey; Jiang, Yannan; Signal, Nada; O'Brien, Daniel; Chen, Jinsong; Murphy, Rinki; Lu, Jun (Frontiers in Nutrition, 2022)
Introduction: Pharmaceutical drugs are beneficial to inflammatory conditions but with side effects, which led to the search for alternative therapies. Perna canaliculus, the New Zealand green-lipped mussel, have shown promise in placebo-controlled trials for inflammatory conditions. Fucoidan, an extract from seaweed Undaria pinnatifida, has been found to have beneficial effects on joint pain and insulin resistance. However, green-lipped mussel and fucoidan have never been combined. Methods and Analysis: A parallel, two-arm, double-blind, randomised, placebo-controlled trial will be conducted in New Zealand to determine whether a food product supplemented with green-lipped mussel and fucoidan improves joint pain and/or insulin resistance. Those who are ethnically Chinese, are aged over 30 years, have prediabetes and hip or knee joint pain will be eligible to participate. They will be randomised at 1:1 ratio to consume either dark chocolate supplemented with 1000 mg mussel powder and 1000 mg fucoidan or dark chocolate with no active substances daily for 100 days. The primary endpoints are change in insulin resistance and patient-reported joint pain. Secondary endpoints include anthropometry, fasting glucose and insulin, HbA1c, inflammatory markers, satiety, quality of life, physical function, pain intensity, and analgesic medication use. A sample size of 150 (75 per arm) will provide 90% power at an overall significance level of 5% (two-sided) to detect a standardised effect size of 0.625 on either of the two co-primary outcomes allowing for 10% loss. Ethics and dissemination: The study was approved by the Health and Disability Ethics Committee (number: 20/STH/153). Results will be made available to participants, funders, and other researchers. Discussion: This trial will provide data on the potential utility of a mussel-fucoidan supplement in reducing joint pain and/or insulin resistance, to inform the development of a supplemented food product suitable for the Chinese market. Trial registration: ANZCTR Registration: ACTRN12621000413820, on 15 April 2021.